2021
DOI: 10.3389/fpls.2020.613004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes and Transcriptional Reprogramming Upon Woody Plant Grafting for Crop Sustainability in a Changing Environment

Abstract: Plant grafting is an ancient agricultural practice widely employed in crops such as woody fruit trees, grapes, and vegetables, in order to improve plant performance. Successful grafting requires the interaction of compatible scion and rootstock genotypes. This involves an intricate network of molecular mechanisms operating at the graft junction and associated with the development and the physiology of the scion, ultimately leading to improved agricultural characteristics such as fruit quality and increased tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 152 publications
(204 reference statements)
0
27
0
Order By: Relevance
“…Besides, considering that grafting practice is frequently used to integrate traits of interest between the rootstock and the scion, which in cacao is mainly destinated to confer disease resistance ( Ribeiro et al, 2016 ), and that the rootstock could alter scion responses to various biotic and abiotic factors ( Jiménez et al, 2013 ; Serra et al, 2014 ; Martínez-Ferri et al, 2019 ; Kapazoglou et al, 2021 ), it is possible that the responses observed here could have been influenced by the root-scion interaction. This may have contributed either to certain variability within each clone, due to the genetic variability of the sexually propagated rootstock, or to a more similar behavior between clones, due to the use of the same rootstock.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, considering that grafting practice is frequently used to integrate traits of interest between the rootstock and the scion, which in cacao is mainly destinated to confer disease resistance ( Ribeiro et al, 2016 ), and that the rootstock could alter scion responses to various biotic and abiotic factors ( Jiménez et al, 2013 ; Serra et al, 2014 ; Martínez-Ferri et al, 2019 ; Kapazoglou et al, 2021 ), it is possible that the responses observed here could have been influenced by the root-scion interaction. This may have contributed either to certain variability within each clone, due to the genetic variability of the sexually propagated rootstock, or to a more similar behavior between clones, due to the use of the same rootstock.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding how plants respond to water stress/scarcity would allow us to inform breeders to select new varieties more resilient to this kind of stress. Hence, many studies on epigenetic changes associated with water stress/scarcity or drought have occurred in recent years both in crops and woody species ( Ashapkin et al, 2020 ; Varotto et al, 2020 ; Kapazoglou et al, 2021 ).…”
Section: Epigenetic Alphabet—(de)coding the Stress Responsementioning
confidence: 99%
“…It has been used for thousands of years to improve performance of many plant species [44]. Transcriptional and epigenetic changes seem to play a central role in phenotypic changes induced by grafting [45,46]. The movement of small RNAs in grafted plants has been demonstrated in many plant species [47,48].…”
Section: Epigenetic Modifications Linked To Graftingmentioning
confidence: 99%
“…Grafting induces significant DNA methylation changes in many plant species [45,51]. Furthermore, locus-specific changes in DNA methylation have been reported in tomato, eggplant and pepper scions using interspecific grafts inherited to the progeny [44].…”
Section: Epigenetic Modifications Linked To Graftingmentioning
confidence: 99%